The INFLUENCE OF THE PROMOTIONAL MIX AND BRAND IMAGE ON THE DECISION TO PURCHASE TOUR AND TRAVEL SERVICES AT PT ARRAFSYAH SAFARI HARAMAIN - Asrifa Iriany B. Pawe (Scientia Integritas Utama, 2022)
Research shows that promotion variables affect positive, significant to the decision of the purchase, proven by a statistical output that reveals a positive and significant value of the purchase decision with a statistical output value With the value of a statistical output that expresses a 0.05 value, the study also states that their image is not a modelling variable (boosters) of promotion influence over decision purchases, it is concluded from data analysis that the immediate impact of influence is greater than the indirect impact.